2009
DOI: 10.1095/biolreprod.108.072066
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Delayed Fatherhood in Mice on Postnatal Development and Behavioral Traits of Offspring1

Abstract: This study aims to analyze, in mice, the long-term effects of delayed fatherhood on postnatal development, spontaneous motor activity, and learning capacity of offspring. Hybrid parental-generation (F(0)) males, at the age of 12, 70, 100, and 120 wk, were individually housed with a randomly selected 12-wk-old hybrid female. The resulting first-generation (F(1)) offspring were tested for several developmental and behavioral variables. Cumulative percentage of F(1) pups that attained immediate righting in the 12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 30 publications
0
41
2
Order By: Relevance
“…Since then, most animal model work related to APA has been based on the mouse. A decrease in learning in the offspring of older sires aged 25-30 months was confirmed, as well as a decrease in motor activity in the offspring of 30 month old sires [20]. Behavioral and brain structural effects have been observed in the offspring of 'younger old' sires as well.…”
mentioning
confidence: 66%
“…Since then, most animal model work related to APA has been based on the mouse. A decrease in learning in the offspring of older sires aged 25-30 months was confirmed, as well as a decrease in motor activity in the offspring of 30 month old sires [20]. Behavioral and brain structural effects have been observed in the offspring of 'younger old' sires as well.…”
mentioning
confidence: 66%
“…This has been examined particularly for the female gametes, or developing embryo (34,38,39), with relatively few examples of paternal programming. However, delaying fatherhood (40)(41)(42)(43), paternal smoking (44,45), and paternal alcohol consumption (46,47) have all been linked to impaired offspring health and longevity. There is some evidence that parental obesity increases the risk of children becoming overweight or obese (48,49), and similarly our initial preliminary observations in the mouse suggest that offspring from obese fathers were heavier before weaning than those from lean fathers.…”
Section: Discussionmentioning
confidence: 99%
“…Another study comparably showed reduced capacity for passive-avoidance learning for offspring of older sires[41] and another found alterations in cortical growth, which are perhaps relevant to the behavioral findings[42]. Both schizophrenia and autism entail reduced learning ability, so these findings may be relevant to the mechanism linking later paternal age to these conditions[35, 43-45].…”
Section: Learning and Intelligencementioning
confidence: 99%